Comparative Analysis of Road Construction Projects Executed by Users’ Committees and Contractors: A Case Study of Shuklagandaki Municipality, Tanahu - Devkota, Bishwas; Aryal, Rajendra; Sapkota, Prashrit; Adhikari, Sundar (Himalayan Journal of Applied Science and Engineering, 2026)
Road construction projects in decentralized local governments are commonly implemented through Users’ Committees and contractor-based procurement approaches; however, empirical evidence comparing their performance at the municipal level in Nepal remains limited. This study aims to compare the performance of road construction projects executed through Users’ Committees and contractors in Shuklagandaki Municipality, Tanahu. Primary data were collected through questionnaire surveys, field observations, and stakeholder consultations covering 42 road construction projects (21 Users’ Committee–executed and 21 contractor-executed), each with a project budget of NPR 2.4 million or above from fiscal year 2078/79 to 2080/81. A comparative quantitative research design was adopted, with respondents selected from Users’ Committee members, contractors, municipal officials, and project beneficiaries using purposive sampling. Data were analysed using descriptive statistics, reliability testing (Cronbach’s alpha), Relative Importance Index (RII), normality testing, and non-parametric analysis employing Kendall’s coefficient of concordance. The results indicate no statistically significant overall performance difference between Users’ Committee–executed and contractor-executed projects (Kendall’s W = 0.171, p = 0.886), leading to acceptance of the null hypothesis. Reliability analysis confirmed acceptable internal consistency across all performance dimensions (Cronbach’s alpha > 0.60). While Users’ Committees perform better in stakeholder engagement, communication, and timely completion, contractor-executed projects demonstrate stronger performance in technical quality, safety measures, and compliance with specifications. The findings suggest that procurement effectiveness is context-dependent rather than universally superior for either approach, supporting the adoption of a context-sensitive procurement strategy by local governments.